Manager's vision for corporate social responsibility - Mamun, Mohammed Abdullah; Ahmed, Zalal Uddin (EuroJournals Publishing, Inc., 2009)
The purpose of the paper was to understand the manager's vision on CSR performance in business of Bangladesh. This study found that the manager's perceptions on CSR were varied from classical to socio-economic views of CSR. The reasons of such variation were contextual changes due to institutional pressures. But the actual CSR performances in the businesses were found poor because of some limitations mentioned by different stakeholders in the study.